Develop mathematical model for biomechanical factors for Proton Saga driver seat - Nur Sabrina Mohd Yusoff (2020)
Automotive industry is the main industrial that leading in Malaysia development towards achieving Industrial Revolution 4.0. Safety will be their very first priority while manufacturing a car. During manufacturing process, external and internal components should be comply with the standard that have been set up by the authority. The most important components for the driver will be their seat. Upon driving for a long journey, drivers tend to feel weak and fatigue as time pass by. As a result, this could lead to accidents. Therefore, aim of the study is to develop mathematical modeling based on the psychophysical and biomechanical factors that contribute to the driver fatigue of Proton Saga. The discomfort area will be investigate through online survey and validate using Minitab software. Meanwhile, as for the relationship of the psychophysical and biomechanical will be analyze by simulator and real road conditions also determine the hardness of the seat foam. Based on obtain parameters, the regression analysis will develop and validate the mathematical model for Proton Saga driver seat as the benefits of mathematical modelling able to simplify complex situations and helps our understanding the real world as certain variables can readily be changed.